Judicial status of Supreme Court of Ukraine as a subject revision of administrative businesses in an ad-ministrative process - Кайдашев, Роман Петрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The judicial order of revision of court decisions in an administrative process is regulated Supreme Court of Ukraine by norms Code of the administrative rule-making of Ukraine and in Code of Ukraine about administrative crimes. In the administrative rule-making regulated Code of the administrative rule-making of Ukraine and broadly speaking is similar to the judicial norms that regulate corresponding activity of Supreme Court of Ukraine in criminal, civil and economic processes. An acceptance of Ukraine of 12.02.2015 of law of Ukraine Supreme soviet is "About providing of right on a just court" stipulated changes in judicial status of Supreme Court of Ukraine at the revision of court decisions, namely it touches his plenary powers and order of revision of administrative businesses. And also changes that changed the place of this instance in the system of judicial bodies of Ukraine took place. Aim of the article - to carry out the analysis of legal status of Supreme Court of Ukraine as a subject of revision of court decisions of administrative courts of Ukraine and resolutions in matters about administrative crimes. In the codes of practice of Ukraine procedure of consideration of statement the higher specialized court is set about the revision of court decisions, in particular requirements are determined to such statement, procedure of her checking for accordance to these requirements and consequences of failure to observe of this procedure and documents that must be added to her, and others like that.. The higher specialized court on this stage is not plenipotentiary to estimate validity of maintenance of statement, he checks up her accordance to the requirements of judicial law, sets in particular, or she is given by the proper subject, or there are the corresponding higher specialized court ruling, and decides a question about the presence of different application the court of appeal instance of the same norm of material right in analogical legal relationships. The feature of legal status of Supreme Court of Ukraine is stipulated by his plenary powers in an administrative process, that is related to the circle of tasks, that it is decided them, namely: a 1) realization of judicial control after identical application of norms of material and judicial right by the administrative courts of more subzero instances; 2) realizations of judicial control after inhibition of Ukraine of international obligations courts during realization of justice in administrative businesses and in matters about administrative crimes. Supreme Court of Ukraine in an administrative process carries out the plenary powers sent to providing of unity of judicial practice (organizational plenary powers) and realization of justice in administrative businesses and during the revision of resolutions in matters about administrative crimes (judicial plenary powers). Organizational plenary powers of Supreme Court of Ukraine will be realized by a way: a 1) providing of unity of judicial practice in an administrative process; 2) realizations of analysis of judicial statistics, generalization of judicial practice; 3) providing of identicalness of application of administrative jurisdiction of norms of right courts and in a method, that certain in Code of the administrative rule-making of Ukraine Code of Ukraine about administrative crimes.